2006
DOI: 10.1002/hep.21231
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of von Willebrand Factor in cirrhosis support platelet adhesion despite reduced functional capacity

Abstract: Cirrhosis of the liver is frequently accompanied by complex alterations in the hemostatic system, resulting in a bleeding tendency. Although many hemostatic changes in liver disease promote bleeding, compensatory mechanisms also are found, including high levels of the platelet adhesive protein von Willebrand Factor (VWF). However, conflicting reports on the functional properties of VWF in cirrhosis have appeared in literature. We have measured a panel of VWF parameters in plasma from patients with cirrhosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
489
2
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(533 citation statements)
references
References 32 publications
29
489
2
13
Order By: Relevance
“…In these patients, the rate of spontaneous recanalization of portal veins was exceptionally high (70%), compared with only 1/41 in the prospective study by Luca et al [202]. Retrospective studies [43,181,203,205] yielded discordant data but overall indicated poorer survival in patients with stable or progressive PVT, if left untreated [2,4,5]. In addition, PVT in liver transplant candidates correlated with increased mortality after liver transplantation [206].…”
Section: Impact Of Portal Vein Thrombosis On the Natural History Of Cmentioning
confidence: 93%
See 2 more Smart Citations
“…In these patients, the rate of spontaneous recanalization of portal veins was exceptionally high (70%), compared with only 1/41 in the prospective study by Luca et al [202]. Retrospective studies [43,181,203,205] yielded discordant data but overall indicated poorer survival in patients with stable or progressive PVT, if left untreated [2,4,5]. In addition, PVT in liver transplant candidates correlated with increased mortality after liver transplantation [206].…”
Section: Impact Of Portal Vein Thrombosis On the Natural History Of Cmentioning
confidence: 93%
“…Patients with cirrhosis present with variable degrees of thrombocytopenia [11] and increased levels of the adhesive protein von Willebrand factor (VWF) which facilitates in vitro platelets to adhere and aggregate normally [2]. When the platelet count was adjusted to a standard value of 100 × 10 9 /L, platelet-rich plasma from patients with cirrhosis generated in vitro as much thrombin as that of healthy subjects [12].…”
Section: Platelet Countmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, the platelet defects get balanced by increased levels of factor VIIIa/vWF, which increases platelet adhesion. 24 Three recent independent studies have been published specifically evaluating the prevalence of deep vein thrombosis (DVT) and pulmonary embolism (PE) in patients with cirrhosis. [25][26][27] The incidence of DVT/PE ranged from 0.5% to 1.87% in these studies.…”
Section: Pathophysiologymentioning
confidence: 99%
“…VWF collagen binding activity was determined with an in-house ELISA assay (intra-and inter-assay CV of 2.9% and 3.8%) as described previously (12). The collagen binding activity of pooled normal plasma was set at 100% and the activity measured in patient samples was expressed as a percentage of pooled normal plasma.…”
Section: Vwf and Adamts13 Assaysmentioning
confidence: 99%